GAMBARAN PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) DALAM BENTUK PINJAMAN ONLINE (PINJOL) PADA UMKM DI INDONESIA - I Made Indra P; Fanny Novika; Antonius Anton Lie; Insri Nuryati (Universitas Bina Bangsa, 2021)
The use of technological advances in the financial sector is growing rapidly. Technological innovations present a more practical financial transaction process, one of which is applied to online loans. Online lending business practices connect lenders with online lenders. The disbursement of 22 trillion loans from 99 online loan companies registered with the OJK has made 9 million transactions to more than 3 million Indonesians. For this reason, it is necessary to analyze the factors that influence interest in using financial technology in the form of online loans. As one of Indonesia's financial drivers, Micro, Small and Medium Enterprises (MSMEs) play a role in transactions using online loan platforms. This study uses a quantitative approach by conducting an online survey of MSMEs to obtain primary data. The survey results show that 44.41% of SMEs use registered online loans, 18.75% use unregistered loans and 36.84% do not. The majority of businesses are SMEs in the culinary field with 58.88% of the main occupations, 50.99% having high school education and 66.78% living in rural areas. From a psychological point of view, most MSME actors make online loans from self-indulgence and have sufficient perceptions, lack of knowledge and sufficient attitudes. From social factors, most of them are motivated by colleagues who use online loans. Most of the MSME sellers are aged 36-45 years with a monthly net income of less than 5 million.